2022
DOI: 10.1038/s41419-022-04707-x
|View full text |Cite
|
Sign up to set email alerts
|

UPF1 contributes to the maintenance of endometrial cancer stem cell phenotype by stabilizing LINC00963

Abstract: Endometrial cancer stem cells (ECSCs) play a vital role in endometrial cancer (EC) metastasis, relapse, and chemoresistance. However, the molecular mechanisms that sustain ECSCs remain elusive. Here, we showed that the expression of UPF1 was upregulated in EC tissues and ECSCs and correlated with poor clinicopathological characteristics. UPF1 silencing suppressed ECSC hallmarks, such as sphere formation ability, carboplatin resistance, migration and invasion, and cell cycle progression. UPF1 regulated the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…As a lncRNA, PVT1 can upregulate the expression of target genes by acting as a competitive endogenous RNA (ceRNA) for miRNA, thereby regulating the malignant biological behavior of tumors. In endometrial cancer, PVT1 can bind to miRNAs, such as miR-612, miR-195-5p, and miR-508-5p, and regulates downstream target genes to promote cancer [ 9 , 10 , 25 ]. In this study, the bioinformatics system predicted and experimentally verified that there is a conserved binding site between the MRE sequence of PVT1 and miR-136.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a lncRNA, PVT1 can upregulate the expression of target genes by acting as a competitive endogenous RNA (ceRNA) for miRNA, thereby regulating the malignant biological behavior of tumors. In endometrial cancer, PVT1 can bind to miRNAs, such as miR-612, miR-195-5p, and miR-508-5p, and regulates downstream target genes to promote cancer [ 9 , 10 , 25 ]. In this study, the bioinformatics system predicted and experimentally verified that there is a conserved binding site between the MRE sequence of PVT1 and miR-136.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UPF1 can regulate the malignant behavior of tumors [ 45 , 46 ], maintain stem cell stemness, and inhibit differentiation [ 23 , 24 , 47 ]. The expression of UPF1 in endometrial cancer tissues is higher than that in adjacent tissues, which can promote the growth and progression of endometrial cancer, increase the activity of the mTOR pathway, inhibit autophagy [ 48 ], and promote the malignant behavior and stemness of ECSCs [ 25 ]. Through our experiments, we identified UPF1 as a downstream gene target of the PVT1/miR-136/Sox2 axis that regulates the malignant behavior and stemness of ECCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, UPF1 can regulate the malignant behavior of tumors [45] [46], maintain stem cell stemness, and inhibit differentiation [23, 24][47, 48]. The expression of UPF1 in endometrial cancer tissues is higher than that in adjacent tissues, which can promote the growth and progression of endometrial cancer, increase the activity of the mTOR pathway, inhibit autophagy [49], and promote the malignant behavior and stemness of ECSCs [25]. Through our experiments, we identi ed UPF1 as a downstream gene target of the PVT1/miR-136/Sox2 axis that regulates the malignant behavior and stemness of ECCs.…”
Section: Discussionmentioning
confidence: 99%
“…NMD may exhibit either pro-tumor and tumor suppressor functions, as a function of cell type, and possibly the genetic context and tumor microenvironment 30 . For example, a reduction in NMD activity, as suggested by downregulation of the key factor UPF1, has been reported in various cancers [31][32][33][34][35][36][37] , in comparison with matched normal tissue; however in other studies of cancerous tissues an overexpression of UPF1 was reported instead 38,39 . A notable case was found in colorectal adenocarcinoma cancer (CRAD), where patients with microsatellite-instability (MSI) hypermutation exhibited overexpression of essential NMD factors such as UPF1/2 and SMG1/6/7, in contrast to microsatellite-stable (MSS) primary CRAD 40 .…”
Section: Introductionmentioning
confidence: 99%